Bipḷabī Dharaṇīdhara - Paṭṭanāẏaka, Jagannātha (Ādibāsī Bhāshā o Saṃskrti Ekāḍemi, Harijana o Ādibāsī Kalyāṇa Bibhāga, 1992)
About Dharaṇīdhara, 1864-1914, leader of 1891 Bhūẏām revolt in Keonjhar, erstwhile princely state and presently a district in Orissa; with a brief history of Keonjhar.